2022
DOI: 10.2147/jhc.s352480
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Transarterial Chemoembolization Plus Tyrosine Kinase Inhibitor for Hepatocellular Carcinoma: a Multicentre Retrospective Study

Abstract: Purpose This study aimed to assess the efficacy and safety of adjuvant transarterial chemoembolization (TACE) plus tyrosine kinase inhibitor (TKI) treatment in patients with hepatocellular carcinoma (HCC) with a high risk of early recurrence after curative resection. Patients and Methods Patients from multiple centres were divided into postoperative adjuvant TACE with (n=57) or without (n=142) TKI administration groups. The disease-free survival (DFS) curve was depicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Most patients are treated with surgical intervention and/or transcatheter arterial embolization. Survival among patients with tumor rupture appeared to be better compared to other groups of advanced HCC 27–29 . Further studies should be conducted to investigate the role of systemic therapy among patients with tumor rupture.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Most patients are treated with surgical intervention and/or transcatheter arterial embolization. Survival among patients with tumor rupture appeared to be better compared to other groups of advanced HCC 27–29 . Further studies should be conducted to investigate the role of systemic therapy among patients with tumor rupture.…”
Section: Discussionmentioning
confidence: 86%
“…Survival among patients with tumor rupture appeared to be better compared to other groups of advanced HCC. [27][28][29] Further studies should be conducted to investigate the role of systemic therapy among patients with tumor rupture. Incidence of peritoneal tumor seeding and the F I G U R E 2 Kaplan-Meier analysis of overall survival between the control and study groups showing that 216 patients during the era of sorafenib reimbursement (study group) had a higher OS at 8.2 months (red dashed line) compared to the control (blue line) ( p = 0.0063).…”
Section: Discussionmentioning
confidence: 99%
“…As sorafenib and other tyrosine kinase inhibitors (TKI) agents are widely used as standard-of-care in the treatment of advanced HCC 31 , the efficacy of sorafenib (the mainly focused TKI agent in published studies) as adjuvant therapy in addition to PA-TACE to prevent recurrence after surgery was remains controversial. It was demonstrated that patients could benefit more from TACE plus TKI agent if they had a tumour diameter 3.5 cm, tumour number less than 3, no BDTT, no hepatic vein tumour thrombus, ruptured tumour, and stage IIIb (American Joint Committee on Cancer 8 th 10 staging system) 32 , 33 . In selected cases, the neo-adjuvant therapies, including TACE, radiofrequency ablation (RFA), stereotactic body radiation therapy (SBRT), and hepatic artery infusion chemotherapy (HAIC), may achieve tumour downstaging facilitating radical surgery and provide beneficial effects.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Lin et al performed a retrospective propensity score matching analysis comparing patients at high risk (tumor > 5 cm with microvascular invasion, ≥ 3 tumor nodules, ruptured HCC, or tumor thrombus in the portal vein, hepatic vein, or bile duct) of recurrence post-hepatectomy who received adjuvant TACE with or without a TKI (sorafenib, lenvatinib, or rivoceranib (apatinib)) [ 25 ]. Patients who received TACE with a TKI had improved 2-year DFS compared to patients who received TACE alone (20.9% vs 12.2%, p = 0.01).…”
Section: Adjuvant Treatmentmentioning
confidence: 99%